The Implementation of the Traditional Game Engklek in Shaping the Social Skills of Elementary School Students - Arif Hidayat; Siti Mariah Ulfah; Nisa Aulia (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to describe the implementation of the traditional engklek game in shaping students' social skills and to explore changes in students' social behavior during the learning process. This research uses a qualitative descriptive approach. The subjects of this study were 19 third-grade students at SD Negeri 119/VI Keroya. Data were collected through observation, interviews, and documentation. The findings indicate that the implementation of the engklek traditional game contributes to the formation of students' social skills. Students demonstrate improvements in communication, cooperation, empathy, and participation during learning activities. In addition, the learning atmosphere becomes more interactive and engaging. Therefore, the engklek traditional game can be used as an alternative approach to support the development of students' social skills in elementary school.